1999
DOI: 10.1523/jneurosci.19-20-08765.1999
|View full text |Cite
|
Sign up to set email alerts
|

Cannabinoids Enhance NMDA-Elicited Ca2+Signals in Cerebellar Granule Neurons in Culture

Abstract: A physiological role for cannabinoids in the CNS is indicated by the presence of endogenous cannabinoids and cannabinoid receptors. However, the cellular mechanisms of cannabinoid actions in the CNS have yet to be fully defined. In the current study, we identified a novel action of cannabinoids to enhance intracellular Ca2+ responses in CNS neurons. Acute application of the cannabinoid receptor agonists R(+)-methanandamide, R(+)-WIN, and HU-210 (1-50 nM) dose-dependently enhanced the peak amplitude of the Ca2+… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
64
2
1

Year Published

2000
2000
2014
2014

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 104 publications
(71 citation statements)
references
References 49 publications
4
64
2
1
Order By: Relevance
“…Our (Howlett, 2005), the majority of these studies identified the involvement of G i/o proteins, which are capable of mobilizing Ca 2 þ via bg-subunit activation of PLC (Sugiura et al, 1996;Netzeband et al, 1999;Rubovitch et al, 2004 In hTM cells, WIN55,212-2 activation of endogenous CB 1 -G q/11 signalling involved activation of PLC and mobilization of Ca 2 þ from thapsigargin and cyclopiazonic acid-sensitive intracellular stores. The possibility of WIN55,212-2 increasing Ca 2 þ in hTM cells through direct inhibition of the sarcoplasmic/endoplasmic reticulum Ca 2 þ ATPase pumps is unlikely as hTM cells were still able to respond to 10 mM ATP with an increase in Ca 2 þ following exposure to WIN55,212-2 (data not shown), a process that is known to require intact Ca 2 þ stores (von Kügelgen and Wetter, 2000).…”
Section: Discussionmentioning
confidence: 91%
“…Our (Howlett, 2005), the majority of these studies identified the involvement of G i/o proteins, which are capable of mobilizing Ca 2 þ via bg-subunit activation of PLC (Sugiura et al, 1996;Netzeband et al, 1999;Rubovitch et al, 2004 In hTM cells, WIN55,212-2 activation of endogenous CB 1 -G q/11 signalling involved activation of PLC and mobilization of Ca 2 þ from thapsigargin and cyclopiazonic acid-sensitive intracellular stores. The possibility of WIN55,212-2 increasing Ca 2 þ in hTM cells through direct inhibition of the sarcoplasmic/endoplasmic reticulum Ca 2 þ ATPase pumps is unlikely as hTM cells were still able to respond to 10 mM ATP with an increase in Ca 2 þ following exposure to WIN55,212-2 (data not shown), a process that is known to require intact Ca 2 þ stores (von Kügelgen and Wetter, 2000).…”
Section: Discussionmentioning
confidence: 91%
“…In primary hippocampal cells, CB1 receptor activation was capable of inhibiting the calcium release, in a cAMP/PKA-dependent manner, from ryanodine-sensitive intracellular store (Zhuang et al, 2005). In contrast, CB1 receptor activation increased NMDA-evoked Ca 2ϩ release from inositol triphosphate (IP 3 )-sensitive intracellular store in cerebellar granule neurons (Netzeband et al, 1999). Therefore, cannabinoids may enhance or inhibit the NMDA-induced increase in Ca 2ϩ levels depending on the cell type, the type of cannabinoid ligands, and the subsequent signaling pathways activated.…”
Section: Amide (Sr141716a) or N-(piperidin-1-yl)-5-(4-iodophenyl)-1-mentioning
confidence: 99%
“…Different and/or additional mechanisms may mediate cannabinoid effects in these brain regions and need to be studied. For example, in cultured cerebellar neurons, cannabinoid receptor activation enhances release from intracellular calcium stores (Netzeband et al 1999). Although this mechanism is unlikely to have a direct effect on transmitter release, it could affect profoundly synaptic transmission through second messenger pathways.…”
Section: Summary Conclusion and Future Directionsmentioning
confidence: 99%